Nerve Regeneration and Functional Recovery With Neurorrhaphy Performed at the Early Distraction Osteogenesis: An Experimental Study. Issue 1 (July 2017) - Kim, Byung Jun; Cho, Jeong Mok; Kwon, Sung Tack
Abstract : Abstract: Distraction osteogenesis is widely used in many clinical situations, but distraction in cases accompanying nerve injury has been avoided due to concern of unfavorable effect on nerve regeneration by traction. This study evaluated the feasibility of early distraction lengthening after neurorrhaphy. Thirty-six rats were evenly distributed into 3 groups (12 rats in each group); neurorrhaphy and distraction (group I), neurorrhaphy and osteotomy without distraction (group II), and only distraction without neurorrhaphy (group III), respectively. After osteotomy on the right tibia, distraction started after 1 week and was continued for 40 days with 0.25 mm per day. Histological evaluation was carried out to identify nerve regeneration at 4, 8, and 12 weeks after surgery. Walking tract analysis was performed to assess the functional recovery preoperatively and 1, 4, 8, and 12 weeks postoperatively. Histologically, axon number ratio was significantly impaired in group I (0.48 ± 0.14) and group II (0.53 ± 0.13) compared with group III (0.88 ± 0.04) at 4 weeks ( P = 0.020). There was no significant difference at both 8 and 12 weeks. Walking tract analysis showed significant differences between groups I and III (−40.5 ± 4.3), and groups II and III (−35.5 ± 5.0) at 1 week ( P = 0.001), but no difference was observed at 8 and 12 weeks. Distraction osteogenesis in early stage after nerve repair is safe and effective, when performed at a rate of 0.25 mm per day in rats.